IMAGE PROCESSING BASED PLANT FERTILIZER SPRAYING ROBOT - KACHARE, Omkar; KALE, Vandana; NARAYAN MOHAPATRA, Badri; NEHE, Nikhil (Journal of process management and new technologies, 2025)
The application of smart technologies in agriculture has transformed conventional farming practices, significantly increasing productivity and sustainability. In this research, we propose a novel method of agricultural automation through the development of an Autonomous Plant Spraying Robot. The system integrates Raspberry Pi and ESP32 microcontrollers along with servo motors to provide a flexible and robust solution for various agricultural operations. The Raspberry Pi functions as the central processing unit, offering substantial computational power and connectivity for real-time data processing and decision-making. The ESP32 microcontroller manages wireless communication and sensor integration, enabling remote monitoring and control of agricultural activities. Servo motors are employed for precise and efficient actuation, allowing the robot to carry out tasks such as spraying, irrigation, and harvesting with high accuracy and consistency. Key features of the project include modular design, scalability, and ease of customization. By leveraging open-source hardware and software platforms, the system remains adaptable and easily integrated with existing agricultural machinery and infrastructure. Furthermore, the use of servo motors enables the robot to navigate a variety of terrains and complex environments, broadening its applicability across diverse farming practices and landscapes. Through field testing and performance evaluation, we demonstrate the effectiveness of the robotic system in enhancing operational efficiency, reducing labor costs, and minimizing environmental impact. Future developments will focus on system optimization, integration of advanced sensing technologies, and real-world deployment to maximize its contribution to global food production.